The Role of the Eastern Press in Supporting the Algerian Revolution: Al-Azhar Magazine as a Model (1954–1962) - Lemghedem, Omar (Journal of Ecohumanism, 2025)
This study analyses the media discourse of Eastern Arab journalism toward the Algerian Revolution through Al-Azhar Magazine. It aims to examine how the Algerian issue was addressed and to identify the forms of support provided at informational, political, religious, and diplomatic levels.Using a descriptive-analytical approach, the study shows that the magazine closely followed the revolution, reported its developments, and exposed French colonial practices.It also highlighted regional and international support, including Maghrebi, Arab, Islamic, and Afro-Asian solidarity within the broader context of decolonization.The study emphasizes the importance of diplomatic efforts in internationalizing the Algerian issue and placing it on the United Nations agenda, reflecting its transformation into an international cause linked to self-determination. It concludes that the magazine’s discourse, combining religious and nationalist dimensions, contributed to mobilizing public opinion and strengthening the legitimacy of the Algerian Revolution.